COMPARATIVE ANALYSIS OF YOUTUBER AND CELEBGRAM IN DEVELOPING CONSUMER BRAND PERCEPTIONS AND INTENTIONS TO BUY LUXURY BRAND COSMETICS - Putri, Irdina Tiara; Astuti, Rifelly Dewi (ASEAN Marketing Journal, 2021)
Manuscript type: Empirical Research Research Aims: This study aims to determine the effect YouTuber and celebgram in the form of parasocial interaction that occurs between the influence to their followers in shaping consumer perceptions and purchase intention for the product that was endorsed by the influencers in the context of luxury cosmetic brand. Methodology: Descriptive quantitave research, total 430 women respondents aged 18 to 34 years, analyzed by using SEM. Research Findings: For both YouTuber and Celebgram all the hypotheses are supported; physical and social attractiveness are found to positively influence the parasocial interaction (PSI). Next, PSI significantly influences the perception of luxury brand that consist of brand value, brand user fit, and brand luxury, further proven to influences purchase intention. Originality: The study is one of study that compares the PSI impact of YouTuber and Celebgram influence toward luxury brand perception and purchase intention. Practitioner Implication: YouTuber and Celebgram are proven have impact toward brand perception and purchase intention so the company could enhance the interaction of the influencer with their followers for example by giving dicsount code by using the name of the influencer in certain time or specific e-commerce merchant. Research limitation: could not see the impact of PSI between responden that watch the influencer’s video compare to others not watch the video, so it is better to do the experiment design in the future.